2016
DOI: 10.1007/s11250-016-1054-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Brazilian red propolis extract on blood metabolites, milk production, and lamb performance of Santa Inês ewes

Abstract: Twenty Santa Inês ewes used to evaluate effects of oral administration of Brazilian red propolis extract on blood metabolites, milk production, and lamb performance were randomly grouped (n = 10 ewes/group) to control without propolis administration and propolis treated (3 g red propolis extract/ewe/day) 21 days before expected lambing date. Blood samples were collected weekly, and daily milk yield was recorded twice weekly until 7 weeks postpartum. Propolis administration increased (P < 0.05) total leukocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 15 publications
2
16
1
1
Order By: Relevance
“…Most of the blood count parameters were not affected by the treatment, except for some WBC parameters. The same response was observed by Beigh et al [37] in their study with lambs fed a cocktail of exogenous fibrolytic enzymes and/or Artemisia absinthium L. (known as wormwood herb), and by Morsy et al [38], who used red propolis extract with antioxidant characteristics to feed Santa Ines ewes; their results showed that the extract or even the plant itself in the diet increased the number of leukocyte counts.…”
Section: Health Parameterssupporting
confidence: 72%
See 1 more Smart Citation
“…Most of the blood count parameters were not affected by the treatment, except for some WBC parameters. The same response was observed by Beigh et al [37] in their study with lambs fed a cocktail of exogenous fibrolytic enzymes and/or Artemisia absinthium L. (known as wormwood herb), and by Morsy et al [38], who used red propolis extract with antioxidant characteristics to feed Santa Ines ewes; their results showed that the extract or even the plant itself in the diet increased the number of leukocyte counts.…”
Section: Health Parameterssupporting
confidence: 72%
“…The results of our study show an increase in the levels of total blood protein and an increase in globulins in animals fed up to 2% yerba mate extract. Morsy et al [38] presented similar results showing that their red propolis extract increased the globulin concentration, which indicates that isoflavonoids found in the extract could activate the immune system of the ewes. Also, the extract used in our work is an important source of caffeine, which is classified as an alkaloid substance, and Chaturvedi et al [48], showed in in vitro cell models that alkaloids components could have immunomodulatory activity.…”
Section: Health Parametersmentioning
confidence: 78%
“…Antibiotics have been used in ruminant nutrition to vastly improve the feed utilization rate and livestock growth (Brown et al ., 2017). However, there is a debate about their use in animal diets due to the increased risk of residual chemicals in meat and milk products, enhancing the development of resistant generations of bacteria (Morsy et al ., 2016). In recent decades, there has been a growing interest in utilizing natural additives that do not represent actual risks to public health (Aguiar et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with our results, Morsy et al . [35] concluded that using extracted red Brazilian propolis (3 g/h/days) to 21 days in Santa Ines ewes before lambing enhanced total leukocyte count while Hb and PCV were not affected. The total WBCs and RBCs were increased while MCV was decreased when New Zealand white bucks fed on 150 mg/kg propolis [36].…”
Section: Discussionmentioning
confidence: 99%
“…Morsy et al . [35] reported that administration of Brazilian red propolis extracts to Santa Ines ewes (3 g/h/days) up to the 21 st day after parturition increased milk yield, fat, protein and lactose yield, and energy corrected milk. In Baladi goats, the same results were found by Emtnan et al .…”
Section: Discussionmentioning
confidence: 99%